Without 'Focus' - Nirit Kadmon; Aldo Sevi (Baltic International Yearbook of Cognition, Logic and Communication, 2010)
It is widely accepted that a notion of 'focus', more or less as conceived of in Jackendoff (1972), must be incorporated into our theory of grammar, as a means of accounting for certain observed correlations between prosodic facts and semantic/pragmatic facts. In this paper, we put forth the somewhat radical idea that the time has come to give up this customary view, and eliminate 'focus' from our theory of grammar. We argue that such a move is both economical and fruitful. Research over the years has revealed that the correlations between prosody, 'focus', and the alleged semantic/pragmatic effects of focus are much less clear and systematic than we may have initially hoped. First we argue that this state of affairs detracts significantly from the utility of our notion of 'focus', to the point of calling into question the very motivation for including it in the grammar. Then we look at some of the central data, and show how they might be analyzed without recourse to a notion of 'focus'. We concentrate on (i) the effect of pitch accent placement on discourse congruence, and (ii) the choice of 'associate' for the so-called 'focus sensitive' adverb only. We argue that our focus-free approach to the data improves empirical coverage, and begins to reveal patterns that have previously been obscured by preconceptions about 'focus'.